Regenerated PET composite material and preparation method thereof

By adding phosphated GO-CS powder to the regenerated PET and performing specific surface treatment, the problem of flammability of traditional regenerated PET materials is solved, and the excellent flame retardant and mechanical properties of the composite material are achieved.

CN119875327AInactive Publication Date: 2025-04-25HANGZHOU KANGHONG IND & TRADE

Patent Information

Application Number
CN202510362403.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional recycled PET materials are flammable, limiting their application in daily life.

Method used

By adding phosphated GO-CS powder to the regenerated PET and performing specific surface treatment and reaction steps during the preparation of the modified regenerated PET, a composite material with excellent flame retardant properties is formed.

Benefits of technology

The flame retardant and mechanical properties of composite materials are improved, making them safer and more reliable to be applied to various fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of regenerated PET (Polyethylene Terephthalate) materials, in particular to a regenerated PET composite material and a preparation method thereof. The regenerated PET composite material is prepared from the following raw materials in parts by weight: 70 to 80 parts of regenerated PET, 10 to 20 parts of modified regenerated PET, 10 to 15 parts of compatilizer, 5 to 15 parts of flexibilizer, 1 to 2 parts of antioxidant and 1 to 2 parts of lubricant. The regenerated PET composite material provided by the invention has excellent flame retardant property and mechanical property, and the fiber obtained by melt spinning of the regenerated PET composite material has excellent flame retardant property and excellent mechanical property, can be widely applied to the textile field, and provides a new direction for recycling of waste polyester materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recycled PET materials, and in particular to a recycled PET composite material and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (PET) has good chemical stability and high strength, and is widely used in textiles and clothing, automotive interiors, civil engineering, etc. However, with the increase in polyester fiber production and the continuous expansion of its application areas, the stock of waste polyester textiles in my country continues to grow, and its comprehensive recycling rate is less than 15%, resulting in serious waste of resources and solid waste pollution.

[0003] Patent technology document CN119060267A discloses a recycled PET composite material and its preparation method. The recycled PET composite material described in the invention includes recycled PET, fluorinated acrylate, chain extender, initiator, thermal conductive filler, glass fiber, fluorinated silane coupling agent, toughening agent, lubricant, antioxidant, and thermal stabilizer. The recycled PET is chain extended and thickened and fluorinated and grafted, and the glass fiber is surface treated with a fluorinated silane coupling agent. The recycled PET composite material finally melt-extruded has high strength, high toughness, and resistance to electrical tracking.

[0004] Patent technical document CN114369351A discloses a high thermal conductivity recycled PC / PET composite material and its preparation method. The invention gives the material high thermal conductivity and is low cost, environmentally friendly and efficient, and is suitable for industrial production applications.

[0005] However, since PET itself has a low limiting oxygen index and is a molten combustible material, this drawback limits its application in daily life. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a recycled PET composite material and a preparation method thereof to solve the problem that traditional recycled PET materials are flammable.

[0007] Based on the above purpose, the present invention provides a recycled PET composite material, comprising the following raw materials in parts by weight: 70-80 parts of recycled PET, 10-20 parts of modified recycled PET, 10-15 parts of a compatibilizer, 5-15 parts of a toughening agent, 1-2 parts of an antioxidant, and 1-2 parts of a lubricant; The preparation steps of the modified recycled PET are as follows: S1: Dispersing chitosan in deionized water to obtain a chitosan solution, dispersing graphene oxide in deionized water to obtain a graphene oxide dispersion, then slowly adding the graphene oxide dispersion to the chitosan solution, reacting at 60-70°C for 24-30 h, centrifuging, filtering, and drying to obtain GO-CS powder; S2: GO-CS powder is dispersed in triethyl phosphite, ultrasonically vibrated for 1-2 h, and then the mixture is transferred to an oil bath and refluxed at 150-160 °C for 36-40 h in a nitrogen atmosphere. After the reaction is completed, the obtained product is centrifuged, filtered, washed, and dried to obtain phosphated GO-CS powder; S3: The regenerated DMT, ethylene glycol and manganese acetate are mixed and added to the reactor, and reacted at 150-180°C for 120-130 minutes to obtain a solution containing BHET; then the phosphated GO-CS powder is dispersed in the ethylene glycol solution, stirred evenly and transferred to the reactor, and reacted at 230-240°C for 30-40 minutes to obtain a solution containing phosphated GO-CS powder, and finally the solution containing BHET and the solution containing phosphated GO-CS powder are mixed, transferred to the reactor, antimony trioxide, trimethyl phosphate and titanium dioxide are added, and reacted at 90-100 Pa and 250-270°C for 160-170 minutes, and then cooled, pelletized and dried to obtain modified recycled PET; The weight ratio of chitosan to graphene oxide in step S1 is 8-10 g:0.4-0.5 g; The usage ratio of GO-CS powder and triethyl phosphite in step S2 is 5-10 g:800-900 ml; The weight ratio of the regenerated DMT, ethylene glycol, phosphated GO-CS powder, manganese acetate, antimony trioxide, trimethyl phosphate and titanium dioxide in step S3 is 100-110 g: 70-80 g: 5-7 g: 1.5-1.8 g: 2.3-2.4 g: 0.08-0.1 g: 1.4-1.5 g.

[0008] Preferably, the recycled PET is a plastic bottle crushing and washing material, with a melt index of 270°C and a density of 1.36-1.39 g / cm 3 .

[0009] Preferably, the compatibilizer is one of styrene-acrylonitrile-glycidyl methacrylate and ethylene-methyl acrylate-glycidyl methacrylate terpolymers.

[0010] Preferably, it is characterized in that the toughening agent is one of methyl methacrylate-butadiene-styrene copolymer and methyl methacrylate-silicone rubber copolymer.

[0011] Preferably, the antioxidant is one of antioxidant 1076 and TASA.

[0012] Preferably, the lubricant is one of stearic acid, calcium stearate, paraffin and polyethylene wax.

[0013] Preferably, the particle size of the graphene oxide in step S1 is 0.2-10 μm.

[0014] Preferably, the drying in step S1 is freeze-drying.

[0015] Preferably, the washing in step S2 is performed using tetrahydrofuran, deionized water and N,N-dimethylformamide.

[0016] Furthermore, the graphene oxide in step S1 is a single-layer graphene oxide purchased from Shanghai Lianghan Nanotechnology Development Co., Ltd. with a product number of LH-GO-01.

[0017] Preferably, the regenerated DMT in step S5 is purchased from Zhejiang Jiaren New Materials Co., Ltd.

[0018] Furthermore, the present invention also provides a method for preparing a recycled PET composite material, comprising the following steps: (1) Drying the recycled PET, then uniformly mixing it with the modified recycled PET, a compatibilizer, a toughening agent, an antioxidant, and a lubricant, and extruding and granulating to obtain composite granules; (2) The composite pellets are injection molded to obtain a composite material.

[0019] Beneficial effects of the present invention: The recycled PET composite material of the present invention, by adding phosphated GO-CS powder, utilizes the good biocompatibility and chemical activity of chitosan itself and the high specific surface area and high stability of graphene oxide, so that the composite material has excellent flame retardant properties and mechanical properties.

[0020] The recycled PET composite material of the present invention adds phosphated GO-CS powder during the preparation process of the modified recycled PET, so that the phosphated GO-CS powder exists in the internal network of the polymer, and the phosphated GO-CS powder can be more evenly dispersed in the entire matrix, thereby improving the mechanical properties and flame retardant properties of the composite material.

[0021] The recycled PET composite material of the present invention is prepared by loading chitosan on the surface of graphene oxide to obtain phosphated GO-CS powder by phosphating. The graphene oxide and chitosan play a synergistic role in the combustion process, so that the mechanical properties and flame retardant properties of the composite material are improved to a certain extent. DETAILED DESCRIPTION

[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0023] Example 1: A recycled PET composite material, the specific preparation steps are as follows: (1) 8 g of chitosan was dispersed in 400 ml of deionized water to obtain a chitosan solution, and 0.4 g of graphene oxide was dispersed in 400 ml of deionized water to obtain a graphene oxide dispersion. The graphene oxide dispersion was then slowly added to the chitosan solution, vigorously stirred and refluxed at 60 ° C for 24-30 h, centrifuged, filtered, and freeze-dried for 2 days to obtain GO-CS powder; (2) Disperse 5 g of GO-CS powder in 800 ml of triethyl phosphite and ultrasonically vibrate for 1 h. Then transfer the mixture to an oil bath and reflux it at 150 °C in a nitrogen atmosphere for 36 h. After the reaction is completed, centrifuge and filter the obtained product, wash it repeatedly with tetrahydrofuran, deionized water and N,N-dimethylformamide, and finally dry it under vacuum freezing conditions for 2 days to obtain phosphated GO-CS powder. (3) 100 g of regenerated DMT, 60 g of ethylene glycol and 1.5 g of manganese acetate were added to a reactor and reacted at 150 °C for 120 min to obtain a solution containing BHET; (4) Disperse 5 g of phosphated GO-CS powder in 10 g of ethylene glycol solution, stir evenly, and transfer to a reactor. React at 230 °C for 30 min to obtain a solution containing phosphated GO-CS powder; (5) The solution containing BHET and the solution containing phosphated GO-CS powder were mixed and transferred to a reactor, 2.3 g antimony trioxide, 0.08 g trimethyl phosphate and 1.4 g titanium dioxide were added, and the mixture was reacted at a vacuum temperature of 90 Pa and 250 ° C for 160 min. After cooling, pelletizing and drying, modified recycled PET was obtained. (6) drying 70 g of recycled PET, and then uniformly mixing the dried 70 g of recycled PET with 10 g of modified recycled PET, 10 g of styrene-acrylonitrile-glycidyl methacrylate, 5 g of methyl methacrylate-butadiene-styrene copolymer, 1 g of antioxidant 1076, and 1 g of polyethylene wax, and extruding and granulating the mixture to obtain composite pellets; (7) The composite pellets are injection molded to obtain a composite material.

[0024] Example 2: A recycled PET composite material, the specific preparation steps are as follows: (1) 9 g of chitosan was dispersed in 500 ml of deionized water to obtain a chitosan solution, and 0.45 g of graphene oxide was dispersed in 450 ml of deionized water to obtain a graphene oxide dispersion. The graphene oxide dispersion was then slowly added to the chitosan solution, vigorously stirred and refluxed at 65 °C for 25 h, centrifuged, filtered, and freeze-dried for 3 days to obtain GO-CS powder; (2) Disperse 7 g of GO-CS powder in 850 ml of triethyl phosphite and ultrasonically vibrate for 2 h. Then transfer the mixture to an oil bath and reflux it at 155 °C in a nitrogen atmosphere for 38 h. After the reaction is completed, centrifuge and filter the product, wash it repeatedly with tetrahydrofuran, deionized water and N,N-dimethylformamide, and finally dry it under vacuum freezing conditions for 2 days to obtain phosphated GO-CS powder. (3) 105 g of regenerated DMT, 64 g of ethylene glycol and 1.6 g of manganese acetate were added to a reactor and reacted at 160 °C for 125 min to obtain a solution containing BHET; (4) Disperse 6 g of phosphated GO-CS powder in 11 g of ethylene glycol solution, stir evenly, and transfer to a reactor. React at 235 °C for 35 min to obtain a solution containing phosphated GO-CS powder; (5) The solution containing BHET and the solution containing phosphated GO-CS powder were mixed and transferred to a reactor, 2.4 g antimony trioxide, 0.09 g trimethyl phosphate and 1.45 g titanium dioxide were added, and the mixture was reacted at a vacuum temperature of 95 Pa and 260 ° C for 165 min. After cooling, pelletizing and drying, modified recycled PET was obtained. (6) drying 75 g of recycled PET, and then uniformly mixing the dried 75 g of recycled PET with 15 g of modified recycled PET, 12 g of styrene-acrylonitrile-glycidyl methacrylate, 10 g of methyl methacrylate-butadiene-styrene copolymer, 1.5 g of antioxidant 1076, and 1.5 g of polyethylene wax, and extruding and granulating to obtain composite pellets; (7) The composite pellets are injection molded to obtain a composite material.

[0025] Example 3: A recycled PET composite material, the specific preparation steps are as follows: (1) Disperse 10 g of chitosan in 600 ml of deionized water to obtain a chitosan solution, then disperse 0.5 g of graphene oxide in 500 ml of deionized water to obtain a graphene oxide dispersion, then slowly add the graphene oxide dispersion to the chitosan solution, vigorously stir and reflux at 70 °C for 30 h, centrifuge, filter, and freeze-dry for 3 days to obtain GO-CS powder; (2) Disperse 10 g of GO-CS powder in 900 ml of triethyl phosphite and ultrasonically vibrate for 2 h. Then transfer the mixture to an oil bath and reflux it at 160 °C in a nitrogen atmosphere for 40 h. After the reaction is completed, centrifuge and filter the product, wash it repeatedly with tetrahydrofuran, deionized water and N,N-dimethylformamide, and finally dry it under vacuum freezing conditions for 2 days to obtain phosphated GO-CS powder. (3) 110 g of regenerated DMT, 68 g of ethylene glycol and 1.8 g of manganese acetate were added to a reactor and reacted at 180 °C for 130 min to obtain a solution containing BHET; (4) Disperse 7 g of phosphated GO-CS powder in 12 g of ethylene glycol solution, stir evenly, and transfer to a reactor. React at 240 °C for 40 min to obtain a solution containing phosphated GO-CS powder; (5) The solution containing BHET and the solution containing phosphated GO-CS powder were mixed and transferred to a reactor, 2.4 g antimony trioxide, 0.1 g trimethyl phosphate and 1.5 g titanium dioxide were added, and the mixture was reacted at a vacuum of 100 Pa and 270 ° C for 170 min. After cooling, pelletizing and drying, modified recycled PET was obtained; (6) drying 80 g of recycled PET, and then uniformly mixing the dried 80 g of recycled PET with 20 g of modified recycled PET, 15 g of styrene-acrylonitrile-glycidyl methacrylate, 15 g of methyl methacrylate-butadiene-styrene copolymer, 2 g of antioxidant 1076, and 2 g of polyethylene wax, and extruding and granulating the mixture to obtain composite pellets; (7) The composite pellets are injection molded to obtain a composite material.

[0026] Comparative Example 1: A recycled PET composite material, which differs from Example 2 in that it does not contain graphene oxide, and the specific preparation steps are as follows: (1) Disperse 7 g of chitosan in 850 ml of triethyl phosphite and ultrasonically vibrate for 2 h. Then transfer the mixture to an oil bath and reflux it at 155 °C in a nitrogen atmosphere for 38 h. After the reaction is completed, centrifuge and filter the resulting product. Wash it repeatedly with tetrahydrofuran, deionized water and N,N-dimethylformamide, and finally dry it under vacuum freezing conditions for 2 days to obtain phosphated CS powder. (2) 105 g of regenerated DMT, 64 g of ethylene glycol and 1.6 g of manganese acetate were added to a reactor and reacted at 160 °C for 125 min to obtain a solution containing BHET; (3) Disperse 6 g of phosphated CS powder in 11 g of ethylene glycol solution, stir evenly, and transfer to a reactor. React at 235 °C for 35 min to obtain a solution containing phosphated CS powder; (4) The solution containing BHET and the solution containing phosphated CS powder were mixed and transferred to a reactor, 2.4 g antimony trioxide, 0.09 g trimethyl phosphate and 1.45 g titanium dioxide were added, and the mixture was reacted at a vacuum temperature of 95 Pa and 260 ° C for 165 min. After cooling, pelletizing and drying, modified recycled PET was obtained. (5) drying 75 g of recycled PET, and then uniformly mixing the dried 75 g of recycled PET with 15 g of modified recycled PET, 12 g of styrene-acrylonitrile-glycidyl methacrylate, 10 g of methyl methacrylate-butadiene-styrene copolymer, 1.5 g of antioxidant 1076, and 1.5 g of polyethylene wax, and extruding and granulating to obtain composite pellets; (6) The composite pellets are injection molded to obtain a composite material.

[0027] Comparative Example 2: A recycled PET composite material, the difference between Example 2 and Example 2 is that there is no chitosan, and the specific preparation steps are as follows: (1) Disperse 7 g of graphene oxide in 850 ml of triethyl phosphite and ultrasonically vibrate for 2 h. Then transfer the mixture to an oil bath and reflux it at 155 °C in a nitrogen atmosphere for 38 h. After the reaction is completed, centrifuge and filter the resulting product. Wash it repeatedly with tetrahydrofuran, deionized water and N,N-dimethylformamide, and finally dry it under vacuum freezing conditions for 2 days to obtain phosphated GO powder. (2) 105 g of regenerated DMT, 64 g of ethylene glycol and 1.6 g of manganese acetate were added to a reactor and reacted at 160 °C for 125 min to obtain a solution containing BHET; (3) Disperse 6 g of phosphated GO powder in 11 g of ethylene glycol solution, stir evenly, and transfer to a reactor. React at 235 °C for 35 min to obtain a solution containing phosphated GO powder; (4) The solution containing BHET and the solution containing phosphated GO powder were mixed and transferred to a reactor, 2.4 g antimony trioxide, 0.09 g trimethyl phosphate and 1.45 g titanium dioxide were added, and the mixture was reacted at a vacuum of 95 Pa and 260 ° C for 165 min. After cooling, pelletizing and drying, modified recycled PET was obtained; (5) drying 75 g of recycled PET, and then uniformly mixing the dried 75 g of recycled PET with 15 g of modified recycled PET, 12 g of styrene-acrylonitrile-glycidyl methacrylate, 10 g of methyl methacrylate-butadiene-styrene copolymer, 1.5 g of antioxidant 1076, and 1.5 g of polyethylene wax, and extruding and granulating to obtain composite pellets; (6) The composite pellets are injection molded to obtain a composite material.

[0028] Comparative Example 3: A recycled PET composite material, the difference from Example 2 is that the phosphated GO-CS powder is directly added, and the specific preparation steps are as follows: (1) 9 g of chitosan was dispersed in 500 ml of deionized water to obtain a chitosan solution, and 0.45 g of graphene oxide was dispersed in 450 ml of deionized water to obtain a graphene oxide dispersion. The graphene oxide dispersion was then slowly added to the chitosan solution, vigorously stirred and refluxed at 65 °C for 25 h, centrifuged, filtered, and freeze-dried for 3 days to obtain GO-CS powder; (2) Disperse 7 g of GO-CS powder in 850 ml of triethyl phosphite and ultrasonically vibrate for 2 h. Then transfer the mixture to an oil bath and reflux it at 155 °C in a nitrogen atmosphere for 38 h. After the reaction is completed, centrifuge and filter the product, wash it repeatedly with tetrahydrofuran, deionized water and N,N-dimethylformamide, and finally dry it under vacuum freezing conditions for 2 days to obtain phosphated GO-CS powder. (3) 90 g of recycled PET was dried, and then mixed evenly with 2.9 g of phosphated GO-CS powder, 12 g of styrene-acrylonitrile-glycidyl methacrylate, 10 g of methyl methacrylate-butadiene-styrene copolymer, 1.5 g of antioxidant 1076, and 1.5 g of polyethylene wax, and extruded and granulated to obtain composite pellets; (4) The composite pellets are injection molded to obtain a composite material.

[0029] Comparative Example 4: A recycled PET composite material, which differs from Example 2 in that no phosphated GO-CS powder is added, and the specific preparation steps are as follows: (1) 90 g of recycled PET was dried, and then mixed evenly with 12 g of styrene-acrylonitrile-glycidyl methacrylate, 10 g of methyl methacrylate-butadiene-styrene copolymer, 1.5 g of antioxidant 1076, and 1.5 g of polyethylene wax, and extruded and granulated to obtain composite granules; (2) The composite pellets are injection molded to obtain a composite material.

[0030] Comparative Example 5: A recycled PET composite material, the specific preparation steps are as follows: (1) 7 g of CS powder was dispersed in 850 ml of triethyl phosphite and ultrasonically vibrated for 2 h. The mixture was then transferred to an oil bath and refluxed at 155 °C for 38 h under a nitrogen atmosphere. After the reaction was completed, the product was centrifuged, filtered, and repeatedly washed with tetrahydrofuran, deionized water, and N,N-dimethylformamide. Finally, it was dried under vacuum freezing conditions for 2 days to obtain phosphated CS powder. (2) 105 g of regenerated DMT, 64 g of ethylene glycol and 1.6 g of manganese acetate were added to a reactor and reacted at 160 °C for 125 min to obtain a solution containing BHET; (3) Disperse 6 g of phosphated CS powder in 11 g of ethylene glycol solution, stir evenly, and transfer to a reactor. React at 235 °C for 35 min to obtain a solution containing phosphated CS powder; (4) The solution containing BHET and the solution containing phosphated CS powder were mixed and transferred to a reactor, 2.4 g antimony trioxide, 0.09 g trimethyl phosphate and 1.45 g titanium dioxide were added, and the mixture was reacted at a vacuum temperature of 95 Pa and 260 ° C for 165 min. After cooling, pelletizing and drying, modified recycled PET was obtained. (5) drying 75 g of recycled PET, and then uniformly mixing the dried 75 g of recycled PET with 15 g of modified recycled PET, 0.45 g of graphene oxide, 12 g of styrene-acrylonitrile-glycidyl methacrylate, 10 g of methyl methacrylate-butadiene-styrene copolymer, 1.5 g of antioxidant 1076, and 1.5 g of polyethylene wax, and extruding and granulating to obtain composite pellets; (6) The composite pellets are injection molded to obtain a composite material.

[0031] Performance Testing Limiting oxygen index: According to GB / T2406-93, "Plastic Combustion Performance Test Method Oxygen Index Method", the limiting oxygen index test is carried out. The test results are shown in Table 1; Vertical combustion level: According to GB2409-84 "Flame retardant performance test method - vertical combustion method", the obtained sample is pressed into a sample strip using a micro injection molding machine. The size of the sample strip is 100 mm, 6.5 mm wide, and 3 mm thick. The distance between the sample strip and the base is adjusted to 30.0 cm, and absorbent cotton is placed at the base. Use a fire source to continuously act on the bottom of the recycled polyester sample strip for 10 seconds, wait for it to extinguish, and then act again for 10 seconds. During the process, record the experimental phenomena and data to determine the vertical combustion level of the sample. The test results are shown in Table 1; The obtained composite material was melt-spun to obtain 83 dtex / 36 f fiber samples, and the performance of the fiber samples was tested: Tensile strength: The tensile test was carried out using a fiber strength extensometer. The test conditions were: clamp spacing 500 mm, temperature 20±2 ℃, relative humidity 65±3%, and tensile speed 10 cm / min. The test results are shown in Table 1. Fiber flame retardancy: The test was conducted according to “FZ / T 50017-2011 Test method for flame retardancy of polyester fiber - oxygen index method”. A fiber with a mass of about 0.30 g was weighed and twisted using a yarn twisting machine with the twist number set to about 60 twists. The yarn bundle was then folded in the middle to a length of 10 cm. The test results are shown in Table 1.

[0032] Table 1 Performance test results Limiting oxygen index (%) Vertical burning level Tensile strength (cN / dtex) Yarn burning loss length (cm) Example 1 34.5 V-0 5.26 0.91 Example 2 36.1 V-0 5.35 0.83 Example 3 35.2 V-0 5.31 0.93 Comparative Example 1 26.7 V-1 4.65 1.85 Comparative Example 2 24.4 V-2 4.45 3.16 Comparative Example 3 30.7 V-0 5.02 1.45 Comparative Example 4 19.2 V-1 4.01 4.21 Comparative Example 5 30.2 V-0 4.87 1.68 Data analysis: It can be seen from the data of Examples 1-3 in the table that the recycled PET composite material of the present invention has excellent flame retardant properties, and its fiber preparation also has excellent flame retardant properties and mechanical properties, and can be widely used in the textile field.

[0033] It can be seen from the data of Example 2 and Comparative Examples 1 and 2 in the table that when preparing phosphated GO-CS powder, when graphene oxide or chitosan is not contained, the mechanical properties and flame retardant properties of the composite material will be affected. This is mainly because chitosan has good biocompatibility and chemical activity, can improve the compatibility between graphene oxide and PET matrix, reduce the interface defects between the two, and can be physically entangled with the PET molecular chain, so that the mechanical properties of the composite material are improved. Graphene oxide itself, as a two-dimensional nanomaterial, can improve the mechanical properties of the composite material, and graphene oxide itself has a certain flame retardant effect. They can form a physical barrier during combustion to prevent flame spread and heat conduction. At the same time, its excellent high temperature stability can maintain the structural integrity of the composite material to a certain extent, thereby making the composite material have excellent flame retardant properties.

[0034] It can be seen from the data of Example 2 and Comparative Examples 3 and 4 in the table that the present invention adds phosphated GO-CS powder during the preparation of modified recycled PET so that the phosphated GO-CS powder exists in the internal network of the polymer. On the one hand, it can be more evenly dispersed in the entire matrix without agglomeration, and can also form stronger chemical bonding and physical entanglement with the PET molecular chain, so that the mechanical properties of the composite material are significantly improved; on the other hand, when the phosphated GO-CS is evenly distributed in the polymer network, it can not only more effectively cover the entire material surface and provide more comprehensive protection, but also maintain the structural integrity of the composite material to a certain extent, thereby delaying the thermal degradation process of PET at high temperature and reducing the generation of volatile products, thereby improving the overall flame retardant properties.

[0035] It can be seen from the data of Example 2 and Comparative Example 5 in the table that the present invention loads chitosan on the surface of graphene oxide, and after adding the phosphated GO-CS powder obtained by phosphating, the mechanical properties and flame retardant properties of the composite material are improved to a certain extent. This may be because the loading makes the graphene oxide have better compatibility, and at the same time, the loading makes the overall grafted phosphorus element more, and the loading can make the graphene oxide and chitosan play a synergistic role in the combustion process, forming a denser and more stable carbon layer, further improving the mechanical properties and flame retardant effect of the composite material.

[0036] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A recycled PET composite material, characterized in that: The raw materials include the following parts by weight: 70-80 parts of recycled PET, 10-20 parts of modified recycled PET, 10-15 parts of compatibilizer, 5-15 parts of toughening agent, 1-2 parts of antioxidant, and 1-2 parts of lubricant; The preparation steps of the modified recycled PET are as follows: S1: Dispersing chitosan in deionized water to obtain a chitosan solution, dispersing graphene oxide in deionized water to obtain a graphene oxide dispersion, then slowly adding the graphene oxide dispersion to the chitosan solution, reacting at 60-70°C for 24-30 h, centrifuging, filtering, and drying to obtain GO-CS powder; S2: GO-CS powder is dispersed in triethyl phosphite, ultrasonically vibrated for 1-2 h, and then the mixture is transferred to an oil bath and refluxed at 150-160 °C for 36-40 h in a nitrogen atmosphere. After the reaction is completed, the obtained product is centrifuged, filtered, washed, and dried to obtain phosphated GO-CS powder; S3: The regenerated DMT, ethylene glycol and manganese acetate are mixed and added to the reactor, and reacted at 150-180°C for 120-130 minutes to obtain a solution containing BHET; then the phosphated GO-CS powder is dispersed in the ethylene glycol solution, stirred evenly and transferred to the reactor, and reacted at 230-240°C for 30-40 minutes to obtain a solution containing phosphated GO-CS powder, and finally the solution containing BHET and the solution containing phosphated GO-CS powder are mixed, transferred to the reactor, antimony trioxide, trimethyl phosphate and titanium dioxide are added, and reacted at 90-100 Pa and 250-270°C for 160-170 minutes, and the modified recycled PET is obtained after cooling, pelletizing and drying; The weight ratio of chitosan to graphene oxide in step S1 is 8-10 g:0.4-0.5 g; The usage ratio of GO-CS powder and triethyl phosphite in step S2 is 5-10 g:800-900 ml; The weight ratio of the regenerated DMT, ethylene glycol, phosphated GO-CS powder, manganese acetate, antimony trioxide, trimethyl phosphate and titanium dioxide in step S3 is 100-110 g: 70-80 g: 5-7 g: 1.5-1.8 g: 2.3-2.4 g: 0.08-0.1 g: 1.4-1.5 g.

2. The recycled PET composite material according to claim 1, characterized in that: The recycled PET is a plastic bottle crushing and cleaning material, with a melting index of 270°C and a density of 1.36-1.39 g / cm 3 .

3. The recycled PET composite material according to claim 1, characterized in that: The compatibilizer is one of styrene-acrylonitrile-glycidyl methacrylate and ethylene-methyl acrylate-glycidyl methacrylate terpolymers.

4. The recycled PET composite material according to claim 1, characterized in that: The toughening agent is one of methyl methacrylate-butadiene-styrene copolymer and methyl methacrylate-silicone rubber copolymer.

5. The recycled PET composite material according to claim 1, characterized in that: The antioxidant is one of antioxidant 1076 and TASA.

6. The recycled PET composite material according to claim 1, characterized in that: The lubricant is one of stearic acid, calcium stearate, paraffin and polyethylene wax.

7. The recycled PET composite material according to claim 1, characterized in that: The particle size of the graphene oxide in step S1 is 0.2-10 μm.

8. A method for preparing a recycled PET composite material according to any one of claims 1 to 7, characterized in that: The steps include: (1) Drying the recycled PET, then uniformly mixing it with the modified recycled PET, a compatibilizer, a toughening agent, an antioxidant, and a lubricant, and extruding and granulating to obtain composite granules; (2) The composite pellets are injection molded to obtain a composite material.

Citation Information

Patent Citations

  • High-thermal-conductivity regenerated PC / PET composite material and preparation method thereof

    CN114369351A

  • Regenerated PET composite material and preparation method thereof

    CN119060267A

  • Preparation method of graphene based reinforced and flame-retarded recycled polyester staple fiber

    CN104630928A

  • Raphene-modified polyester blended fabrics and preparation method thereof

    CN107190382A

  • Copolymerization modification method for graphene depth degradation of waste polyester textile

    CN109096497A

Cited By

  • Preparation method of marine regenerated PET (Polyethylene Terephthalate) environment-friendly clothing fastener

    CN120623728A

  • A method for preparing environmentally friendly clothing fasteners made from marine recycled PET

    CN120623728B